1988
DOI: 10.3109/02699058809150936
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy and the neurobehavioural sequelae of traumatic brain injury

Abstract: Recent advances in clinical neuropharmacology are likely to improve the treatment and rehabilitation of traumatic brain injury (TBI) patients. Treatment may be directed to alleviate specific symptoms, to improve function in certain areas, or even to enhance the cortical recovery process. The author reviews pertinent issues in clinical neuropharmacology for the following drug classes: stimulants, other dopamine agonists, antidepressants, lithium, cholinergics, neuroleptics, anticonvulsants, beta-blockers, calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(20 citation statements)
references
References 141 publications
1
19
0
Order By: Relevance
“…It is plausible that clinicians and parents perceived that ADHD symptoms would resolve in children who had no preinjury history of ADHD. In the absence of placebo-controlled, randomized clinical trials of pharmacologic treatment of the behavioral sequelae of TBI in children, the extant preliminary studies [22][23][24][25] provide only a suggestion that stimulants may be effective. With residual ADHD symptoms in our SADHD group and persistent high levels of symptoms in those children with preinjury ADHD, our results indicate the need for controlled treatment studies that stratify the randomization according to preinjury ADHD.…”
Section: Treatment With Stimulant Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that clinicians and parents perceived that ADHD symptoms would resolve in children who had no preinjury history of ADHD. In the absence of placebo-controlled, randomized clinical trials of pharmacologic treatment of the behavioral sequelae of TBI in children, the extant preliminary studies [22][23][24][25] provide only a suggestion that stimulants may be effective. With residual ADHD symptoms in our SADHD group and persistent high levels of symptoms in those children with preinjury ADHD, our results indicate the need for controlled treatment studies that stratify the randomization according to preinjury ADHD.…”
Section: Treatment With Stimulant Medicationsmentioning
confidence: 99%
“…8 The literature consists of a retrospective chart review of 10 children treated with methylphenidate after sustaining TBI and a crossover, placebo-controlled clinical trial. [22][23][24][25] In view of the findings of Mahalick et al 24 that methylphenidate produced cognitive gains over 1 week relative to placebo and performance with placebo did not differ from pretreatment baseline, there is justification for further clinical trials. Although the 2003 National Survey of Children's Health conducted by the Centers for Disease Control and Prevention 26 recorded that 56% of 4.4 million children age 4 to 17 years who had been diagnosed with developmental ADHD had been treated at some time with stimulants, and a recent population-based, birth cohort study 27 reported that 77% of children diagnosed with ADHD by DSM-IV criteria had been treated with stimulants by age 17 years, there are sparse data concerning the current practice of pharmacologic management of ADHD symptoms following TBI in children.…”
mentioning
confidence: 99%
“…Drugs inhibiting apoptosis, blocking glutamate-induced excitotoxicity, or attenuating oxidative stress were designed to reduce cell loss with the premise that neuronal sparing would enhance recovery (Faden et al, 1989; Jennings et al, 2008). Unfortunately, the neuroprotective effects observed in the TBI laboratories have not translated successfully to the clinic (Gualtieri, 1988; Tolias and Bullock, 2004). In contrast, therapeutics used during the rehabilitative phase have shown more promise in addressing long-term disability, although they do not necessarily demonstrate the same level of neuroprotection as drugs designed to inhibit apoptosis or block excitotoxicity (Gualtieri, 1988; Rees et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the neuroprotective effects observed in the TBI laboratories have not translated successfully to the clinic (Gualtieri, 1988; Tolias and Bullock, 2004). In contrast, therapeutics used during the rehabilitative phase have shown more promise in addressing long-term disability, although they do not necessarily demonstrate the same level of neuroprotection as drugs designed to inhibit apoptosis or block excitotoxicity (Gualtieri, 1988; Rees et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, a significant pharmacotherapy that has consistently shown benefits to attention, behavioral outcomes, executive functions, and memory is dopaminergic (DA) therapy [6][8], but the aspect of TBI pathology targeted by DA therapy remains unclear. Pharmacological interventions to elucidate cognitive and behavioral deficits in patients with head injuries are now being performed clinically, although empirical studies supporting this practice are limited [9], [10], and the use of psychostimulant drugs (e.g., methylphenidate) for head injuries [11], [12] may indicate that cognitive and learning impairments are related to a deficiency in the dopamine system after head injury. Furthermore, according to a statement in a recent clinical trial of amantadine in treating head injuries that was published in NEJM in 2012 [8], future research should focus on determining the pathophysiological characteristics of patients who responded to amantadine, the most effective dosage, and the duration of treatment and timing of its initiation, as well as the effectiveness of amantadine in patients with brain injuries.…”
Section: Introductionmentioning
confidence: 99%